Mass concrete composite anti-crack structure and crack control construction method based on mass concrete composite anti-crack structure
By using composite crack-resistant structures and multi-field coupling models in large-volume concrete structures for crack risk assessment, combined with calcium-magnesium composite expansion agent and hydration heat temperature rise control materials, the problem of non-load cracks in large-volume concrete structures is solved, and the effect of reducing cracking risks and improving durability is achieved, while controlling construction and maintenance costs.
Patent Information
- Application Number
- CN202311148308.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-06
- Publication Date
- 2025-03-07
AI Technical Summary
Large-volume concrete structures are prone to non-load cracks during construction, resulting in reduced structural durability and increased maintenance costs. It is difficult for the existing technology to effectively control cracks and control construction costs.
A large-volume concrete composite crack-resistant structure is adopted, including the ordinary concrete layer in the core, the outer side crack-resistant concrete layer, the steel bar mesh and the top crack-resistant concrete layer. The crack risk assessment is carried out through the "hydration-temperature-humidity-constraint" multi-field coupling model, the concrete mix ratio is optimized, and the calcium-magnesium composite expansion agent and hydration heat temperature rise control material is used, and a special specification of galvanized steel bar mesh is combined to ensure the bonding performance and stress uniformity of the concrete.
It effectively reduces the risk of concrete cracking, improves the durability of concrete, controls construction costs and later maintenance costs, and improves the overall quality of large-volume concrete projects.
Smart Images

Figure CN119571916A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of building engineering construction, and specifically relates to a large-volume concrete composite anti-cracking structure and a crack control construction method based thereon. Background Art
[0002] At present, with the rapid development of bridge, large-scale housing construction and other projects, concrete cracks have always been a major problem in large-volume structures. When the concrete structure cracks, the corrosion rate of the corrosive medium will also be greatly accelerated, and the durability of the concrete structure will be further deteriorated. In severe cases, the structural stress will be affected, and the service life will eventually be reduced. At the same time, the later maintenance cost will also be significantly increased. Therefore, concrete crack control is the premise for ensuring the service life of structural concrete, and controlling non-load cracks during the construction period is the key.
[0003] The cracking of large-volume concrete mainly manifests as vertical cracks on the surface, and in severe cases, vertical through cracks appear. Cracks generally occur in the early stage of construction - from the time when the concrete is finally set to 90 days. Most of the existing studies on concrete cracking are qualitative analyses, and temperature and shrinkage are considered to be important factors causing early cracking. At present, there is still a lack of systematic theoretical analysis and quantitative research on hydration heat temperature rise, temperature stress, and concrete shrinkage, which will cause problems such as unreasonable design of structural systems or crack-resistant structures, inappropriate construction process and maintenance methods, leading to the generation and development of cracks and causing engineering risks.
[0004] How to prevent harmful cracks from occurring in large-volume structural concrete during construction, improve the durability of concrete, and not excessively increase construction costs, has become a major technical problem encountered in large-volume concrete construction today. Temperature stress and deformation load are closely related to major factors such as concrete engineering structure design, external temperature changes, construction technology, raw material characteristics, and later thermal insulation and moisture maintenance measures. During the construction process, large stress concentration due to temperature and cracks caused by deformation loads are the main factors. Although my country has a large number of engineering practices in controlling cracks in large-volume concrete, such as the use of cooling water pipe systems, air-cooled aggregates, and large amounts of mineral admixtures and fibers in concrete. However, although these measures have effectively reduced some cracks to a certain extent and reduced later maintenance costs, they have also excessively increased construction costs. Summary of the invention
[0005] In view of the above-mentioned problems existing in the prior art, the present invention provides a large-volume concrete composite anti-cracking structure and a large-volume concrete crack control method based thereon, which, on the one hand, reduces the risk of concrete cracking and improves the durability of the overall concrete structure; on the other hand, effectively controls the construction cost and operation and maintenance cost, thereby facilitating the promotion and use of large-volume concrete projects.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] A large-volume concrete composite anti-cracking structure, comprising: a core ordinary concrete layer, an outer side anti-cracking concrete layer, a steel mesh disposed between the interfaces of the two, and a top anti-cracking concrete layer, wherein the steel mesh is tied and fixed with steel bars, and the height of the steel mesh after being tied with the steel bars is higher than the outer side anti-cracking concrete layer;
[0008] The pouring height of the anti-cracking concrete layer on the outer side is 20 to 30 cm higher than the ordinary concrete layer in the core, and when pouring reaches the elevation of the interface between the two concrete layers at the top, pour the top anti-cracking concrete layer;
[0009] The steel mesh is a specially processed galvanized steel mesh, and the side length of the square aperture of the steel mesh is 10-15 mm, and φ1.5-2.5 mm.
[0010] The galvanized steel mesh adopts an aperture side length in the range of 10 to 15 mm. If the side length is less than 10 mm, the concrete slurry is not easy to pass through, resulting in poor bonding performance of the two concrete contact surfaces and uneven stress on the entire structure; if the aperture side length is greater than 15 mm, the anti-cracking concrete poured first will flow through the aperture to the ordinary concrete area, resulting in an increase in the cost of concrete materials.
[0011] The galvanized steel mesh has a diameter of 1.5 to 2.5 mm. If φ is less than 1.5 mm, the isolation mesh has low rigidity and is easily deformed during pouring. Large holes are easily formed at local locations on the contact surface, resulting in a large number of internal defects in the concrete, causing poor bonding between the two types of concrete, thereby affecting the overall uniformity of force on the concrete. If φ is greater than 2.5 mm, on the one hand, it increases the construction cost, and on the other hand, it affects the crack resistance of the two types of concrete.
[0012] The anti-cracking concrete layer on the outer side and the top anti-cracking concrete layer adopts anti-cracking concrete, and the apparent density of the concrete is 2350-2450 kg / m 3 , including the following components, each component weight is:
[0013]
[0014]
[0015] The anti-cracking agent is composed of the following components by weight percentage:
[0016]
[0017] The sum of the weight percentages of the aforementioned components is 100%.
[0018] The pouring height of the anti-cracking concrete layer on the outer side adopts the "hydration-temperature-humidity-constraint" multi-field coupling model cracking risk assessment software, and the cracking risk is tensile stress / tensile strength. When the concrete cracking risk coefficient is not greater than 0.7, the structural concrete will definitely not crack; when the concrete cracking risk coefficient is greater than 1.0, the structural concrete will definitely crack; when the concrete cracking risk coefficient is between 0.7 and 1.0, the structural concrete has a certain cracking risk, and it is necessary to reduce the cracking risk through measures such as strengthening maintenance. Under the condition that the concrete cracking risk coefficient is less than 0.7, the height of the anti-cracking concrete on the outer side and the thickness of the anti-cracking concrete layer on the top are calculated.
[0019] Temperature-deformation sensors are arranged at the core of the core ordinary concrete layer, at the interface between the core ordinary concrete layer and the steel mesh, at the interface between the outer side anti-cracking concrete layer and the steel mesh, and at the core of the outer side anti-cracking concrete layer parallel to the steel mesh direction to monitor the temperature-deformation development changes of concrete at different positions and ensure the uniformity of force in the composite structure of the two types of concrete.
[0020] The present invention also provides a mass concrete crack control construction method based on the mass concrete crack-resistant composite structure, comprising the following steps:
[0021] (1) First, based on the multi-field coupling mechanism and model of concrete "hydration-temperature-humidity-constraint", the cracking risk of the composite anti-crack structure was evaluated, and the pouring height of the side and top anti-crack concrete layer was quantitatively analyzed;
[0022] (2) Optimize the concrete mix design based on the crack risk assessment results to design crack-resistant concrete with low temperature rise and high crack resistance;
[0023] (3) The steel mesh is tied to the fixed steel bars and placed between the outer side anti-cracking concrete layer and the core ordinary concrete layer. The height of the steel mesh after being tied to the fixed steel bars is higher than the outer side anti-cracking concrete layer;
[0024] (4) Carry out continuous pouring in horizontal layers and oblique sections according to the actual site elevation;
[0025] (5) Use the inclined surface segmented layered pouring method, first pour the outer side anti-cracking concrete layer to a certain height and vibrate it, then pour the core ordinary concrete layer to a certain height and vibrate it, and always ensure that the pouring height of the outer side anti-cracking concrete layer is 20 to 30 cm higher than the core ordinary concrete layer, and repeat the process;
[0026] (6) When pouring to the elevation of the interface between the two concretes at the top, the entire top surface is then made of anti-cracking concrete, thereby obtaining a composite anti-cracking structure for controlling cracks in large-volume concrete.
[0027] After the pouring in step (6) is completed, the side surface is cured with a wooden formwork for not less than 7 days, and the thickness of the formwork is not less than 1.5 cm. During the curing period, an insulation layer structure is added outside the formwork according to the change of ambient temperature to ensure that the overall temperature drop rate of the concrete is ≤2°C / d; the permanent exposed surface of the top anti-cracking concrete layer adopts a water storage curing method in the early stage, and a curing method of covering with insulation cotton wool + rainproof cloth is adopted in winter, and the curing time is not less than 14 days.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) Based on the multi-field coupling mechanism and model of concrete "hydration-temperature-humidity-constraint", the cracking risk of large-volume composite structures is assessed, and the height of crack-resistant concrete that needs to be poured on the side and top surfaces is quantitatively analyzed;
[0030] (2) By adding calcium oxide and magnesium oxide composite expansion agents, the two complement each other to regulate the expansion development process of concrete, achieving phased and full-process compensation shrinkage;
[0031] (3) By adding hydration heat temperature rise control materials, the process of rapid hydration heat release period is optimized and adjusted, reducing the stress concentration caused by temperature;
[0032] (4) Use galvanized steel mesh of special specifications to improve the bonding performance of the two concretes on the one hand, and ensure the uniformity of the overall force of the composite structure composed of the two concretes on the other hand, with fewer internal defects in the concrete, while also controlling the construction cost;
[0033] (5) When pouring, pour a certain height of anti-cracking concrete first, and then pour ordinary concrete, to ensure that the height of the anti-cracking concrete is always higher than that of ordinary concrete, to ensure the uniformity of the transfer of shrinkage stress of the two different concretes at the interface, and to avoid stress concentration problems;
[0034] (6) After pouring, the top surface is maintained by an economical and efficient water storage and heat preservation method in summer, and by covering with heat preservation cotton batting and rainproof cloth in winter. The side surface is maintained by a wooden mold, and a cooling water pipe is used inside to reduce the temperature, achieving the effect of "lowering the temperature inside and protecting the outside";
[0035] (7) The composite structure of ordinary concrete in the core and anti-cracking concrete in the outer side reduces the risk of cracking of large-volume concrete structures, improves the overall construction quality of the concrete structure, saves construction costs, and reduces subsequent maintenance costs.
[0036] Working principle of the present invention:
[0037] The present invention discloses a large-volume concrete composite anti-cracking structure. Based on the concrete "hydration-temperature-humidity-constraint" multi-field coupling mechanism and model, the cracking risk of the composite structure is evaluated, and the thickness of the side and top anti-cracking concrete casting is quantitatively analyzed; through the dual control technology of calcium-magnesium composite expansion agent and hydration heat temperature rise control material, the expansion process is optimally matched with the temperature process and the shrinkage process, and low-temperature rise and high-cracking resistance concrete is prepared. On the one hand, the calcium-magnesium composite expansion agent is used, and the two complement each other to regulate the expansion development process of the concrete, which can compensate for the plastic shrinkage and autogenous shrinkage of the concrete in the early stage, and can compensate for the temperature drop shrinkage, autogenous shrinkage and drying shrinkage of the concrete in the later stage, thereby realizing the staged and full-process compensation shrinkage, especially the compensation for the shrinkage generated in the temperature drop stage, which significantly weakens the stress concentration of the concrete. On the one hand, the hydration heat temperature rise control material is used to optimize and adjust the process of the hydration rapid heat release period. In addition, the hydration heat temperature rise control material and the cooling water pipe water flow work together to cool down, taking away a large amount of heat during the hydration rapid heat release period, reducing the stress concentration caused by temperature; the concrete interface uses a galvanized steel mesh of special specifications, on the one hand to improve the bonding performance of the two concretes, on the other hand to ensure the overall stress stability of the composite structure composed of the two concretes, so that the shrinkage stress of the two concretes is transmitted uniformly, the stress gradient is reduced, and the internal defects of the concrete can be reduced; after the pouring is completed, the top surface adopts an economical and efficient water storage and heat preservation and moisture maintenance method in summer, and a heat preservation and moisture maintenance method of covering with heat preservation cotton wool + rainproof cloth in winter, and the side surface adopts heat preservation and maintenance with wooden molds, achieving the effect of "inside reduction and outside protection". Through the comprehensive application of the above technologies, the risk of concrete cracking is reduced, the durability of concrete is improved, and the construction cost and later maintenance costs are saved. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a schematic diagram of the large-volume concrete composite anti-cracking structure of the present invention.
[0039] Figure 2 It is a schematic diagram of the tying method of the galvanized steel mesh and steel bars described in the present invention.
[0040] Figure 3 It is a schematic diagram of the material distribution method in the large-volume concrete composite anti-cracking structure of the present invention.
[0041] Figure 4 This is the temperature monitoring result of Example 1 described in the present invention.
[0042] Figure 5 This is the deformation monitoring result of Example 1 described in the present invention.
[0043] Figures 1 to 3 The markings are: 1 steel bar, 1-1 horizontal bar, 1-2 main bar, 1-3 wire mesh, 1-4 hook bar, 2 steel mesh, 3 outer side anti-cracking concrete layer, 4 core concrete layer. DETAILED DESCRIPTION
[0044] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with specific embodiments, but the content of the present invention is not limited to the following embodiments.
[0045] Example 1
[0046] The anchor structure is 75.0m long, 80.0m wide and 44.0m high. The total concrete volume is 250,000 cubic meters. It is a large-volume concrete structure, and the 60d strength assessment and acceptance are adopted. The anchor is cast in layers, and the risk of concrete cracking is extremely high. Vertical temperature cracking has occurred. Therefore, it is necessary to improve the overall crack resistance of the anchor concrete structure, improve the durability of the engineering structure, and control the construction cost and operation and maintenance costs. It mainly includes the following steps:
[0047] Firstly, based on the multi-field coupling mechanism and model of concrete "hydration-temperature-humidity-constraint", the cracking risk of the composite structure was assessed, and a quantitative analysis showed that the pouring thickness of the anti-cracking concrete on the side and top surfaces was 2m and 1.5m respectively.
[0048] According to the results of cracking risk assessment, the concrete mix ratio is optimized and designed to achieve low temperature rise and high crack resistance concrete. The concrete has low hydration heat temperature rise in the early stage and compensatory shrinkage performance in the whole process in stages. The mix ratio of cementitious materials for single cubic meter concrete is determined to be 202 kg of Conch P·LH 42.5 (low heat) cement, 138 kg of Class I fly ash, and 30 kg of Subot composite anti-cracking agent. The expansive agent is composed of calcium oxide and magnesium oxide with different activities. The free calcium oxide in the calcium oxide expansive agent is 60%, and the active reaction time of the magnesium oxide expansive agent is 120s to 300s. The cement hydration regulating material in the anti-cracking agent accounts for 3% of the anti-cracking agent.
[0049] The interface is made of galvanized steel mesh processed with special specifications. The side length of the square hole of the steel mesh is 10.5mm and the wire is φ1.5mm.
[0050] Temperature-deformation sensors are arranged parallel to the length direction of the steel mesh in the core of ordinary concrete, the interface of ordinary concrete, the interface of anti-crack concrete, and the core of anti-crack concrete to monitor the development and changes of concrete temperature-deformation at different positions.
[0051] When pouring, first pour the anti-cracking concrete to a height of 50cm and vibrate, then pour the ordinary concrete to a height of 30cm and vibrate, always ensuring that the pouring height of the anti-cracking concrete is 20 to 30cm higher than that of ordinary concrete, and repeat the process in sequence.
[0052] When the top surface is poured to the elevation of the interface between the two concretes, the entire top surface is constructed with anti-cracking concrete, and the thickness of each layer of anti-cracking concrete is 50cm.
[0053] After pouring, the side surface was cured with wooden formwork for 7 days, the thickness of the formwork was 2.4 cm, and the overall temperature drop rate of the concrete was 1.8℃ / d; the permanent exposed surface of the top anti-cracking concrete was cured with water storage in the early stage, and the curing time was 20 days. The concrete deformation results are as follows:
[0054] During the temperature rise stage, the maximum expansion deformation of the center height of ordinary concrete is 274με, and the unit temperature rise expansion deformation is 10.8με / ℃; the maximum expansion deformation of the center height of anti-crack concrete is 440με, and the unit temperature rise expansion deformation is 22με / ℃; the maximum deformations in the length direction of the center of ordinary concrete, the ordinary concrete side at the interface, the anti-crack concrete side at the interface, and the center of anti-crack concrete are 226με, 303με, 284με, and 333με, respectively, and the unit temperature rise expansion deformation in the length direction is 9.3με / ℃, 11.8με / ℃, 11.6με / ℃, and 15.8με / ℃, respectively. According to the monitoring results, the expansion deformation in the length direction shows a law of gradually decreasing from the outside to the inside, and the deformations on both sides of the interface are basically the same, and there is no stress concentration problem; the temperature drop is too high. During the monitoring process, the shrinkage deformation of ordinary concrete in the height direction due to temperature drop is 10.5με / ℃, and the shrinkage deformation of anti-cracking concrete in the height direction due to temperature drop is 10.4με / ℃. The unit temperature drop shrinkage of the two concretes is basically the same; the unit temperature drop shrinkage deformation of the ordinary concrete center, the ordinary concrete side at the interface, the anti-cracking concrete side at the interface, and the anti-cracking concrete in the length direction are 10.6με / ℃, 10με / ℃, 9με / ℃, and 7.6με / ℃ respectively. According to the monitoring results, the shrinkage deformation in the length direction shows a gradual increase from the outside to the inside, and there is no stress concentration problem at the interface. During the temperature drop process, the curve is relatively smooth, and there is no jump point phenomenon, indicating that no cracking occurs during the temperature drop process. It can be seen that the use of anti-cracking concrete in the outer layer can significantly improve the crack resistance of the overall structure.
[0055] In summary, the composite anti-cracking structure of the present invention is based on the multi-field coupling mechanism and model of concrete "hydration-temperature-humidity-constraint", and the thickness of the anti-cracking concrete casting on the side and top surfaces is quantitatively analyzed. The side and top surfaces are cast with anti-cracking concrete, and the core is cast with ordinary concrete. The two concretes are cast at the same time. The concrete interface uses a galvanized steel mesh of special specifications, which has a certain rigidity and is not easy to deform. At the same time, it should have a mesh size of a certain size. On the one hand, it improves the bonding performance of the two concretes, and on the other hand, it ensures the overall stress stability of the composite structure composed of the two concretes, so that the shrinkage stress of the two concretes is evenly transferred, and the stress gradient is reduced. At the same time, the internal defects of the concrete can be reduced during the casting process of the steel mesh that is not easy to deform. After the casting is completed, the top surface adopts an economical and efficient water storage insulation and moisture maintenance method in summer, and a covering insulation cotton wool + rainproof cloth insulation and moisture maintenance method in winter. The side surface adopts a wooden mold insulation maintenance method, and the internal cooling water pipe method is used to reduce the temperature, achieving a controllable goal of cracking risk <0.7. Compared with the conventional method used in construction, all concrete adopts crack control methods such as adding anti-cracking fibers or expansion agents, which can greatly reduce construction costs and subsequent maintenance costs, and overall improve the long-term service life of concrete structures.
[0056] The above are only preferred embodiments of the present invention, and cannot be used to limit the scope of rights of the present invention. Therefore, equivalent changes made according to the scope of the patent application of the present invention still fall within the protection scope of the present invention.
Claims
1. A large-volume concrete composite anti-cracking structure, characterized in that: include: A core ordinary concrete layer, an outer side anti-cracking concrete layer, a steel mesh placed between the interfaces of the two, and a top anti-cracking concrete layer, wherein the steel mesh is tied and fixed with the steel bars, and the height thereof after being tied with the steel bars is higher than the outer side anti-cracking concrete layer; The pouring height of the anti-cracking concrete layer on the outer side is 20 to 30 cm higher than the ordinary concrete layer in the core, and when pouring reaches the elevation of the interface between the two concrete layers at the top, pour the top anti-cracking concrete layer; The steel mesh is a specially processed galvanized steel mesh, and the side length of the square aperture of the steel mesh is 10-15mm, and φ1.5-2.5mm; The anti-cracking concrete layer on the outer side and the top anti-cracking concrete layer adopts anti-cracking concrete, and the apparent density of the concrete is 2350-2450 kg / m 3 , including the following components, each component weight is: The anti-cracking agent is composed of the following components by weight percentage: The sum of the weight percentages of the aforementioned components is 100%.
2. A large-volume concrete composite anti-cracking structure according to claim 1, characterized in that: The pouring height of the anti-cracking concrete layer on the outer side adopts the "hydration-temperature-humidity-constraint" multi-field coupling model cracking risk assessment software, and the cracking risk is tensile stress / tensile strength. When the concrete cracking risk coefficient is not greater than 0.7, the structural concrete will definitely not crack; when the concrete cracking risk coefficient is greater than 1.0, the structural concrete will definitely crack; when the concrete cracking risk coefficient is between 0.7 and 1.0, the structural concrete has a certain cracking risk. Under the condition that the concrete cracking risk coefficient is less than 0.7, the height of the anti-cracking concrete on the outer side and the thickness of the anti-cracking concrete layer on the top are calculated.
3. A large-volume concrete composite anti-cracking structure according to claim 2, characterized in that: Temperature-deformation sensors are arranged at the core of the core ordinary concrete layer, at the interface between the core ordinary concrete layer and the steel mesh, at the interface between the outer side anti-cracking concrete layer and the steel mesh, and at the core of the outer side anti-cracking concrete layer parallel to the steel mesh.
4. A crack control construction method based on the large volume concrete crack resistant composite structure according to any one of claims 1 to 3, characterized in that: The steps include: (1) First, based on the multi-field coupling mechanism and model of concrete "hydration-temperature-humidity-constraint", the cracking risk of the composite anti-crack structure was evaluated, and the pouring height of the side and top anti-crack concrete layer was quantitatively analyzed; (2) Optimize the concrete mix design based on the crack risk assessment results to design crack-resistant concrete with low temperature rise and high crack resistance; (3) The steel mesh is tied to the fixed steel bars and placed between the outer side anti-cracking concrete layer and the core ordinary concrete layer. The height of the steel mesh after being tied to the fixed steel bars is higher than the outer side anti-cracking concrete layer; (4) Carry out continuous pouring in horizontal layers and oblique sections according to the actual site elevation; (5) Use the inclined surface segmented layered pouring method, first pour the outer side anti-cracking concrete layer to a certain height and vibrate it, then pour the core ordinary concrete layer to a certain height and vibrate it, and always ensure that the pouring height of the outer side anti-cracking concrete layer is 20 to 30 cm higher than the core ordinary concrete layer, and repeat the process; (6) When pouring to the elevation of the interface between the two concretes at the top, the entire top surface is then made of anti-cracking concrete, thereby obtaining a composite anti-cracking structure for controlling cracks in large-volume concrete.
5. A crack control construction method according to claim 4, characterized in that: After pouring in step (6), the side surface is cured with a wooden formwork for not less than 7 days, and the thickness of the formwork is not less than 1.5 cm. During the curing period, an insulation layer structure is added outside the formwork according to the changes in ambient temperature to ensure that the overall temperature drop rate of the concrete is ≤2°C / d.
6. A crack control construction method according to claim 4, characterized in that: After the pouring in step (6) is completed, the permanently exposed surface of the top anti-cracking concrete layer is maintained by water storage in the early stage, and by covering with insulation cotton wool + rainproof cloth in winter. The maintenance time is not less than 14 days.
Citation Information
Cited By
Anti-crack mass concrete and preparation method thereof
CN120774679A
Synchronous pouring functional gradient type concrete and construction method thereof
CN120867300A
A synchronous casting function gradient type concrete and a construction method thereof
CN120867300B
Reflective heat insulation type railway pier concrete composite structure and construction method thereof
CN120902366A